Two Rieske Fe/S Proteins and TAT System in Mesorhizobium loti MAFF303099: Differential Regulation and Roles on Nodulation - Basile, Laura A.; Zalguizuri, Andrés; Briones, Gabriel; Lepek, Viviana C. (Frontiers in Plant Science, 2018)
Mesorhizobium loti MAFF303099 is a rhizobial strain that nodulates Lotus spp. A Mesorhizobium loti MAFF303099 mutant strain affected in the tatC gene was generated. This strain presented an altered protein secretion level to the culture supernatant and also a higher sensitivity to SDS. Its nodulation phenotype on Lotus showed the induction of small and colorless nodules, and in a larger number than those induced by the wild-type strain. In addition, these nodules presented defects in the degree of occupation by rhizobia. Two Rieske Fe/S proteins, encoded by the mll2707 and mlr0970 genes, were predicted as potential Tat substrates in M. loti MAFF303099. The transcriptional expression of mll2707 and mlr0970 genes was analyzed under different oxygen growth conditions. The mll2707 gene was expressed constitutively, while the expression of the mlr0970 gene was only detected under anaerobic and microaerophilic in vitro conditions. Both genes were down-regulated in the tatC mutant strain. mll2707 and mlr0970 mRNAs from the wild-type strain were detected in nodules. Using a translational reporter peptide fusion, we found that the Mll2707 protein was only detectable in the wild-type strain. On the other hand, although Mlr0970 protein was detected in wild-type and tatC mutant strains, its association with the membrane was favored in the wild-type strain. The tatC and the mll2707 mutant strains were affected in the cytochrome c oxidase activity. These results confirm that Mll2707 is required for cytochrome c-dependent respiration and that Tat functionality is required for the correct activity of Mll2707. The mll2707 mutant strain showed a nodulation phenotype similar to the tatC mutant strain, although it presented only a slight difference in comparison with wild-type strain in terms of nodule occupation. No defective phenotype was observed in the nodulation with the mlr0970 mutant strain. These results indicate that, of the two Rieske Fe/S proteins coded by M. loti MAFF303099, only Mll2707 expression is required for the induction of effective nodules, and that the functionality of the Tat system is necessary not only for the correct function of this protein, but also for some other protein required in an earlier stage of the nodulation process.